The Students' Responses Toward the Use of Google Classroom for Learning Vocabulary In the Higher Education - Mada Gymnastiar Andy Nugraha; Mohamad Irvansyah Satria Yudha; Dian Fadhilawati (Universitas Islam Balitar, 2023)
This study was undertaken with the aim of eliciting students' perspectives concerning the utilization of Google Classroom as an instructional platform for enhancing vocabulary in the realm of higher education. Employing a descriptive quantitative methodology, the investigation was carried out among a cohort of 19 students in their fourth academic semester, all of whom were actively enrolled in the English Education Department at Blitar Islamic University. The primary research tool was a questionnaire, The finding revealed a positive inclination among students toward utilizing Google Classroom for vocabulary instruction. The study underscored the efficacy of Google Classroom in facilitating vocabulary acquisition through its interactive features, enabling seamless communication between peers and instructors for the dissemination of vocabulary materials. This is proved by the students' responses, for example;84.2% of students agreed that Google Classroom can be downloaded easily on multiple devices, and another 84.2% of students agreed that they enjoy using Google Classroom for learning vocabulary because of its free accessibility. However, an element of uncertainty persists among students concerning the potential of Google Classroom to either supplement or supplant traditional classroom settings in vocabulary learning activities. This research sheds light on the promising role of technology-enhanced learning platforms like Google Classroom in fostering vocabulary development while also recognizing the need for further exploration of their integration within broader education.